Room-temperature ferromagnetism in two-dimensional transition metal borides: a first-principles investigation. Issue 17 (27th April 2021) - Dou, Min; Li, Huan; Yao, Qingnian; Wang, Jiabao; Liu, Yunfei; Wu, Fang
Abstract : Both CrB and FeB monolayers are FM metals with a moderate magnetic anisotropy energy by saturation with functional groups, which indicates that the 2D transition metal borides have great potential application in information storage devices. Abstract : It is currently technologically important to predict new two-dimensional (2D) ferromagnetic materials for next-generation information storage media. However, discovered 2D ferromagnetic materials are still rare. Here, we explored the fact that 2D transition metal borides are potential room-temperature 2D ferromagnetic materials. By performing first-principles calculations, we found that the CrB monolayer is a ferromagnetic (FM) metal, while the FeB monolayer is a typically antiferromagnetic (AFM) semiconductor. Interestingly, both CrB and FeB monolayers are FM metals with a moderate magnetic anisotropy energy by saturating with functional groups. Monte Carlo simulations show that the Curie temperature ( T c ) of the CrB monolayer is about 520 K, which is further increased to 580 K and 570 K through –F and –OH chemical modification, while T c is about 250 K, 275 K and 300 K for the FeBF, FeBO and FeBOH monolayer, respectively. Thus, the 2D transition metal borides have great potential applications in information storage devices.